Availability of Mahua Flowers and Seeds in Dandakaranya and Prospects of Mahua Oil Industry - Awasthi, R. L. (Indian Forester, 1971)
An attempt has been made to assess the potential of Mahua flowers. and seeds in the Dandakaranya area and the prospects of running a Mahus Oil Mill have been discussed ed.